Principles of pulmonary medicine - Weinberger, Steven E.; Cockrill, Barbara A.; Mandel, Jess (Elsevier, 2019)
With an emphasis on the pathophysiologic basis of pulmonary disease, Principles of Pulmonary Medicine, 7th Edition, by Drs. Steven E Weinberger, Barbara A Cockrill, and Jess Mandel, provides a superbly illustrated introduction to this fast-changing field. This essential text employs a concise and understandable approach, integrating clinical topics with underlying physiologic, pathophysiologic, and basic science concepts critical for medical students, trainees, and those looking for a practical update on both acute and chronic pulmonary diseases